Psychedelics in psychiatric treatment: a literature review - Wolski, Adam; Szplit, Ewa; Patalong, Mikołaj; Cemaga, Roman; Kubicki, Mateusz; Kołodziej, Przemysław; Bruska, Natalia; Błaszkowski, Bartłomiej; Bilyk, Andrii; Więckowska, Katarzyna (Quality in Sport, 2026)
Background: Psychedelic substances have been used for millennia in religious and healing contexts and have recently re-emerged as subjects of scientific interest due to advances in neuroscience and psychiatry. Research suggests that psychedelics may address limitations of conventional psychiatric treatments, particularly in disorders such as major depressive disorder, PTSD, substance use disorders, and anxiety disorders. Aim: This article aims to critically review and synthesize current evidence on the neurobiological mechanisms, therapeutic efficacy, and safety profiles of selected psychedelic substances—psilocybin, LSD, MDMA, and ketamine—in the treatment of psychiatric disorders. Materials and Methods: A literature review was conducted using databases including PubMed, Scopus, and Google Scholar. Clinical trials, meta-analyses, and reviews published in English between 2006 and 2025 were included. Studies addressing therapeutic outcomes, neurobiological mechanisms, and safety considerations of psychedelic-assisted therapies were analysed. Results: In publications included in this literature review, psilocybin demonstrated robust antidepressant effects, benefits in substance use disorders, and reductions in anxiety following limited dosing sessions. MDMA-assisted psychotherapy showed strong efficacy in PTSD, with high remission rates. LSD exhibited promising effects in anxiety and substance use disorders. Ketamine produced rapid antidepressant and anti-suicidal effects in depression and showed potential in addiction and anxiety, although results in PTSD were mixed. Conclusions: Psychedelic-assisted therapies represent a promising and scientifically credible expansion of psychiatric treatment options. While associated risks necessitate careful screening and clinical oversight, evidence supports their role as adjunctive or alternative interventions for selected patients, warranting further large-scale and long-term investigation.